2007
DOI: 10.1029/2006ja012222
|View full text |Cite
|
Sign up to set email alerts
|

Cassini Ion and Neutral Mass Spectrometer data in Titan's upper atmosphere and exosphere: Observation of a suprathermal corona

Abstract: [1] The neutral nitrogen and methane measurements made by Ion and Neutral Mass Spectrometer during Cassini flybys T A , T B , and T 5 in Titan's upper atmosphere and exosphere are presented. Large horizontal variations are observed in the total density, recorded to be twice as large during T A as during T 5 . Comparison between the atmospheric and exospheric data show evidence for the presence of a significant population of suprathermal molecules. Using a diffusion model to simultaneously fit the N 2 and CH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 35 publications
5
122
0
Order By: Relevance
“…For altitudes lower than z 0 , the mixing ratio is taken as zero. Taking into account the high molecular diffusion above the homopause at ∼1200 km (D = 0.5 −−1×10 10 cm 2 s −1 , De La Haye et al 2007;Yelle et al 2008), we also assumed a constant mixing ratio above the homopause z h = 1200 km. With this model, the best fit is obtained Fig.…”
Section: A Thermospheric Casementioning
confidence: 99%
See 1 more Smart Citation
“…For altitudes lower than z 0 , the mixing ratio is taken as zero. Taking into account the high molecular diffusion above the homopause at ∼1200 km (D = 0.5 −−1×10 10 cm 2 s −1 , De La Haye et al 2007;Yelle et al 2008), we also assumed a constant mixing ratio above the homopause z h = 1200 km. With this model, the best fit is obtained Fig.…”
Section: A Thermospheric Casementioning
confidence: 99%
“…The thermal profile used for our computation is a combination of (i) the temperatures measured by Huygens/HASI (Fulchignoni et al 2005) in the troposphere at altitudes between 0-140 km; (ii) the disk-averaged Cassini/CIRS stratospheric temperatures (Vinatier et al 2010) at altitudes between 140-500 km; (iii) the Cassini/INMS retrieved temperatures (i.e. 155 K in average, De La Haye et al 2007) at altitudes between 1000-1500 km; (iv) a decreasing temperature from 165 K to 155 K at altitudes between 500 and 1000 km. Our modeling results, presented below, indicate that the HNC(6-5) line is optically thin (opacity τ ∼ 0.12), therefore results are not too sensitive to the precise temperature profile.…”
Section: Modelingmentioning
confidence: 99%
“…Several processes have been proposed as sources from Titan including thermal escape Bell et al, 2011), chemically-induced escape (De La Haye et al, 2007), slow hydrodynamic escape (Strobel 2008(Strobel , 2009Yelle et al, 2008), pick-up ion loss and ionospheric outflow (Ledvina et al, 2005;Wahlund et al, 2005;Sillanpaa et al, 2006;Ma et al, 2006;Hartle et al, 2006;Coates et al. 2007a;Edberg et al, 2011;Westlake et al, 2012;Coates et al, 2012) and plasma-induced atmospheric sputtering (Shematovich et al, 2003;Michael et al, 2005;De La Haye et al, 2007). …”
Section: Titanmentioning
confidence: 99%
“…On Titan, reliable measurements of corona N 2 and CH 4 made by the Ion Neutral Mass Spectrometer (INMS) on board Cassiniextend up to an altitude of 2000km (De La Haye et al 2007a), whereas measurements of corona H 2 extend up to at least 7000km (Cui et al , 2011. Existing studies revealed no remarkable deviation in exobase temperature of H 2 from the mean temperature in the upper atmosphere (Cui et al , 2011), implying that a hot H 2 population does not exist.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies revealed no remarkable deviation in exobase temperature of H 2 from the mean temperature in the upper atmosphere (Cui et al , 2011), implying that a hot H 2 population does not exist. For N 2 and CH 4 , the analysis of the TA, TB, and T5 INMS data by De La Haye et al (2007a) revealed the presence of suprathermal coronae for both constituents with a typical temperature enhancement of ∼20-70K over the mean state below the exobase. The above distinction calls for certain heating mechanisms to be operative for N 2 and CH 4 , but not for H 2 near Titan's exobase.…”
Section: Introductionmentioning
confidence: 99%